Shopee (ShopeeFood) Application Quality Factors and Their Impact on Loyalty through Consumer Satisfaction - SP, Sri Wiludjeng; Yahya, Tio Yuskar; Pratama, Wilki Mulya; Hardiana, Dandi; Putr, Vincentius Willy Andy; Naibaho, Tongos Marhata (CENTRAL ASIA AND THE CAUCASUS, 2022)
Shopee is one of the marketplaces in Indonesia whose existence continues to increase along with the Shopeefood feature. Shopeefood comes with an online-based food and beverage order service with a wide range of voucher claims so that there is consumer satisfaction and loyalty in the use of Shopee application. This study is a quantitative study, and it aims to find out how respondents respond to the dominant factors of Shopee applications and their impact on loyalty through consumer satisfaction. This study uses a simple factor analysis and regression analysis tool the sampling technique used is random sampling. Respondents of this study are Shopee application consumers who we will invite to take a survey through a questionnaire that we will create (is we avoid Shopee application consumers). The results showed the dominant factor was the convenience factor and had a positive and significant impact on loyalty through satisfaction. Therefore, it is recommended that Shopee Company (Shopeefood) still have to maintain and develop a promotional marketing strategy to stay in the market segment with similar competitors and Shopeefood must further improve in its service.